PENERAPAN DAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PT. NUR HAZANAH KARYA ABADI - Dessy Like Ampnir; Hendri P. Perangin-Angin (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Mining activities can be categorized as activities with high risk of accidents, including accidents that cause a risk of minor injuries to a risk of death. PT. Nur Hazanah Karya Abadi is a company engaged in mining operation with gravel as the main mineral material. The standard operating procedures applied in this company have not matched with the standards of occupational safety and health of mining companies, as mentioned in the regulation of the minister of energy and mineral resource of Indonesia. Moreover, the availability of personal protective equipment in this company is also incomplete and inadequate. Furthermore, the lack of attention from employees regarding the use of personal protective equipment at work also has the potential to create work accidents.